PERSONALITI DAN PENGHARGAAN KENDIRI DALAM KALANGAN KAKITANGAN MAJLIS AGAMA ISLAM MELAKA (MAIM) - Marsam, Erni Najwa Irdayu; Aziz, Syazwana (Jurnal ’Ulwan, 2023)
This study aims to see the relationship between personality and self-esteem among the staff of the Malacca Islamic Religious Council (MAIM). This study involves descriptive and inferential data analysis. The subjects of this study consisted of 20 male employees and 20 female employees who were selected by simple random sampling. The measurement tool used is Big Five Personality - 44 (BFI 44) items to measure personality while the Rosenberg Self Esteem Scale (RSES) measurement tool is used to measure the level of self-esteem of employees. Data was analyzed using the Statistical Package for the Social Science (SPSS). The study data was analyzed using Pearson Correlation analysis. The reliability and validity of this questionnaire is at a high and reliable level, i.e. the Big Five Personality questionnaire is as much as .709, while the Rosenberg Self Esteem Scale (RSES) questionnaire is as much as .815. The findings of the study show that openness personality, thrift personality, extrovert personality, agreeable personality and neuroticism personality have a significant positive relationship with self-esteem. Therefore, the research results obtained through this study can be used by all parties in helping to improve the personality of the employees in improving the quality of a strong personality.